Invertebrados bentônicos: Relação entre estrutura da fauna e características do mesohabitat - Uieda, Virginia Sanches [UNESP] (2016)
The formation of different mesohabitats, such as pools, riffles and runs, is common along the courses of stream ecosystems, and these are frequently accompanied by changes in the benthic fauna structure. In this paper, we analyzed the fauna of benthic invertebrates in riffles and runs of a stretch of the Capivara River (Middle Tietê River Basin). The analyses of the environmental characteristics and samplings of the fauna were performed in three riffles and three runs (five replicates in each) within a month of the rainy season. The mesohabitats differed with respect to the higher percentage of cobble in the runs and greater depth, current and number of boulders in the riffles. Of the total of 57 Operational Taxonomic Unities (OTU's) sampled, 75% were common to both mesohabitats (Morisita Similarity = 0.86). When the percentage of abundance by mesohabitat was analyzed, spatial similarity remained with Hexapoda (> 80%, mainly represented by Ephemeroptera, Diptera and Trichoptera) and Annelida (10%) standing out in abundance. The exploratory analysis (cluster and NMDS) found high spatial similarity, but the results of the Analysis of Similarity (ANOSIM) indicated a significant difference between the mesohabitats (p <0.1%), both when the total OTU's were analyzed or when removing the rare ones. Five groups contributed more greatly to the average dissimilarity between mesohabitats: Simulium and Baetodes were more abundant in riffles, while Traveryphes, Hagenulopsis and Macrelmis were more abundant in runs. Thus, the results of ANOSIM stressed the importance of refining identification for a more precise interpretation of the relationship between fauna and habitat structure.